Reducing Geographical Imbalances of Health Workers in Sub-Saharan Africa : A Labor Market Perspective on What Works, What Does Not, and Why - Lemiere, Christophe; Herbst, Christopher H.; Jahanshahi, Negda; Smith, Ellen; Soucat, Agnes (World Bank, 2012)
This report discusses and analyzes labor market dynamics and outcomes (including unemployment, worker shortages, and urban-rural imbalances of categories of health workers) from a labor economics perspective. It then uses insights from this perspective as a basis for elaborating policy options that incorporate the underlying labor market forces. The goal of the study is to address undesirable outcomes (including urban-rural HRH imbalances) more effectively. The study draws on an extensive inventory of policy options relevant to urban-rural labor force imbalance in Sub-Saharan Africa and the experiences with these imbalances to date. Given the limited documentation available on this topic through formal channels, the review relies heavily on 'gray literature' from policymakers in Sub-Saharan Africa and their development partners, especially the World Bank and the World Health Organization (WHO). The report is divided into five main sections. The first section focuses on economic policies related to Human Resources for Health (HRH) objectives. It argues that policymaking has ignored health labor market dynamics. The second section provides data showing the extent of urban-rural imbalances and describes how these imbalances affect health system outcomes. The third section uses a health labor market framework to explain these imbalances. The fourth section outlines policy options relevant to Sub-Saharan Africa for addressing market distortions and affecting labor market outcomes. It also reviews evidence on the policies, strategies, and programs designed to address geographic imbalances in Sub-Saharan Africa, highlighting what has been done, what has worked, and what has not. The last section provides a roadmap for policymakers.